2017
DOI: 10.2217/imt-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Cancer: Targeting Cancer During Active Disease or During Dormancy?

Abstract: Immunotherapeutic targeting of advanced stage cancers has prolonged the survival of cancer patients, yet its curative efficacy is limited due to tumor immunoediting and escape. On the other hand, human vaccines have been able to eradicate smallpox and control several other infectious diseases. The success has resulted from the administration of vaccines in prophylactic settings, or during latency periods in order to protect an individual during future exposure to the disease rather than curing an established d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The tumor-host interactions are progressively known as crucial constituents of cancer growth or inhibition. Particularly, infiltrating immune cells are critical features of the tumor microenvironment [103]. Cancer cells are encircled by stromal cells, including macrophages, fibroblasts, mast cells, neutrophils, and lymphocytes, which communicate through an intricate system of intercellular signaling pathways, mediated by cytokines, adhesion molecules, and the receptor-ligand network [42].…”
Section: Cancer Immune-mediated Dormancymentioning
confidence: 99%
“…The tumor-host interactions are progressively known as crucial constituents of cancer growth or inhibition. Particularly, infiltrating immune cells are critical features of the tumor microenvironment [103]. Cancer cells are encircled by stromal cells, including macrophages, fibroblasts, mast cells, neutrophils, and lymphocytes, which communicate through an intricate system of intercellular signaling pathways, mediated by cytokines, adhesion molecules, and the receptor-ligand network [42].…”
Section: Cancer Immune-mediated Dormancymentioning
confidence: 99%
“…Immune therapy for dormant micrometastases has been proposed based on preclinical and clinical evidence [371]. Randomized phase II clinical trials of patients with nodepositive or high-risk node-negative Her2 + BC after definitive therapy and no clinical evidence of disease demonstrated a potential clinical benefit in survival [372,373].…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%
“…Cancer cells that are truly dormant after chemotherapy and negative for Ki67 are susceptible to immune modulation, whereas cells that are low for Ki67 are not [374]. Based on these observations, it has been proposed that immunotherapy should be administered after therapeutic conditioning to suppress tumor immunoediting that permits escape from immunotherapy or in combination with targeted therapies [371].…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%
“…Therefore, immunotherapy is the only option for the treatment of tumor dormancy. In fact, we have demonstrated that dormant tumor cells remain highly susceptible to immunotherapy if targeted before clinical recurrence ( 63 ).…”
Section: Immunotherapeutic Targeting Of Tumor Dormancy For the Prevenmentioning
confidence: 99%